A THERORETICAL AND PRACTICAL - METODOLOGICAL APPREACH TO PRIMARY SELECTION IN BASKETBALL - Călin POP; Ioan FEFLEA; Eugen ROȘCA (Editura Universităţii din Oradea, 2017)
The selection is a systematic and continuous process by means of which the specialists aim to identify children with special skills for practicing certain sports, on the basis of certain biological and psychological criteria. It operates continuously and simultaneously to the training process starting from beginner level up to high performances, and implies a set of periodical evaluations intended to emphasize the child's skills to successfully practicing a sport. The selection is a permanent process and is of the utmost importance, since the value of the athlete and implicitly of the team's subsequent performance depends on the quality of such selection. A good selection organization and running shall facilitate the discovery of the children with the highest potential. Otherwise, the coach shall invest work, time and knowledge in preparing certain athletes who later on, upon transition to senior level, would not obtain expected results. The performance is originated in three main sources: athlete's biological and personality value, the intellectual value expressed by the specialists' body managing the training pattern programming, and time. Within this triptych, time is a constant, while the other two sources are variable.